Electrical burns in adults - Al-Benna, S (Acta chirurgiae plasticae, 2023)
INTRODUCTION: Electrical burns account for up to 10% of burns admissions worldwide and are a potentially serious mechanism of injury. The aim of this study is to describe the epidemiology, presentation, management and complications of electrical burn injuries in adults. MATERIAL AND METHODS: A retrospective study of all adult patients with electrical burns admitted to a tertiary burns centre. RESULTS: Eighty-two cases were identified. The mean age was 40 ± 2 years, 92.7% were males. The most common activities causing the injuries were work (39%) and do-it yourself activities (32%). A low voltage (< 1,000 W) power source was involved in 78% of cases. The mean total body surface area involved was 3 ± 0.3%. The head, hands, and other upper extremities were the body parts most frequently injured. The mean hospital stay was 2 ± 1days. CONCLUSION: Electrical injury was an infrequent but potentially serious cause of injury in adults. Minor injuries were successfully managed non-operatively. Electrical burns in adults are mainly low voltage burns contracted by manual workers resulting in a flesh burn. Although rare, the loss of digits, neurological sequelae, cardiac arrhythmias and renal failure remain serious complications in a significant number of cases.
Keywords: dospělí; povrch těla; adult: burns; horní končetina; Female; popáleninové jednotky; Burns, Electric; Adult; ženské pohlaví; Body Surface Area; lidé; popálení elektrickým proudem; Upper Extremity; surgical procedures; retrospektivní studie; operative; Male; Burns; electric; Burn Units; mužské pohlaví; Retrospective Studies; Humans